Effect of cyclooxygenase inhibitors on gentamicin-induced nephrotoxicity in rats - Hosaka,E.M. (2004)
The frequent use of nonsteroidal anti-inflammatory drugs (NSAID) in combination with gentamicin poses the additional risk of nephrotoxic renal failure. Cyclooxygenase-1 (COX-1) is the main enzyme responsible for the synthesis of renal vasodilator prostaglandins, while COX-2 participates predominantly in the inflammatory process. Both are inhibited by non-selective NSAID such as indomethacin. Selective COX-2 inhibitors such as rofecoxib seem to have fewer renal side effects than non-selective inhibitors. The objective of the present study was to determine whether the combined use of rofecoxib and gentamicin can prevent the increased renal injury caused by gentamicin and indomethacin. Male Wistar rats (250-300 g) were treated with gentamicin (100 mg/kg body weight, ip, N = 7), indomethacin (5 mg/kg, orally, N = 7), rofecoxib (1.4 mg/kg, orally, N = 7), gentamicin + rofecoxib (100 and 1.4 mg/kg, respectively) or gentamicin + indomethacin (100 and 5 mg/kg, respectively, N = 8) for 5 days. Creatinine clearance and alpha-glutathione-S-transferase concentrations were used as markers of renal injury. Animals were anesthetized with ether and sacrificed for blood collection. The use of gentamicin plus indomethacin led to worsened renal function (0.199 ± 0.019 ml/min), as opposed to the absence of a nephrotoxic effect of rofecoxib when gentamicin plus rofexicob was used (0.242 ± 0.011 ml/min). These results indicate that COX-2-selective inhibitors can be used as an alternative treatment to conventional NSAID, especially in situations in which risk factors for nephrotoxicity are present.